Functional and numerical responses and reproduction of Campoletis flavicincta parasitizing Spodoptera frugiperda caterpillars - doi: 10.4025/actasciagron.v35i4.15871 (Acta Scientiarum. Agronomy, 2013)
The functional and numerical responses, reproductive characteristics, and viability of Campoletis flavicincta (Hymenoptera: Ichneumonidae) as well as the mortality after parasitism of the host Spodoptera frugiperda (Lepidoptera: Noctuidae) were analyzed in the laboratory. Campoletis flavicincta pairs were maintained until female death with 10, 20, 30, 40, or 50 caterpillars day-1 of the host S. frugiperda. A type III functional response curve was fitted to the average number of caterpillars supplied per day during the female wasp lifespan, as the explanatory variable. The handling time was 0.5940 ± 0.0875h, and the instantaneous search 0.0047 ± 0.0020 h-1. The functional response for each of the first five days of the host was a type III. The longevity at the five host densities and the parasitism rate showed a significant linear decrease with the host density. The offspring production showed an increasing quadratic variation with increased host density. The production of females by C. flavicincta, the offspring sex ratio, the viability of the parasitoid pupae and the percentage of mortality of S. frugiperda caterpillars were not affected by host density. The functional and numerical responses of C. flavicincta indicate that this parasitoid could be a candidate for biological control of S. frugiperda.